Influence of LiBO2 addition on the microstructure and lithium-ion conductivity of Li1+xAlxTi2−x(PO4)3(x = 0.3) ceramic electrolyte. Issue 6 (15th April 2018) - Bai, Hainan; Hu, Jiulin; Li, Xiaoguang; Duan, Yusen; Shao, Feng; Kozawa, Takahiro; Naito, Makio; Zhang, Jingxian
Abstract: Concerning the safety problems of conventional Li-ion batteries with liquid electrolytes, it is crucial to develop reliable solid-state electrolytes with high ionic conductivity. Li1+x Alx Ti2−x (PO4 )3 (LATP, x = 0.3) is regarded as one of the most promising solid electrolytes due to its high ionic conductivity and excellent chemical stability to humidity. Herein, a new strategy is proposed for improving the sintering behavior and enhancing the ionic conductivity of LATP by using LiBO2 as the sintering aid via liquid phase sintering. The as-prepared sample LATP with homogeneous microstructure and high relative density of 97.1% was successfully synthesized, yielding high total ionic conductivity of 3.5 × 10 −4 S cm −1 and low activation energy of 0.39 eV at room temperature. It was found that the addition of LiBO2 could effectively enhance the densification and increase the ionic conductivity of LATP electrolyte, proving an effective way to synthesis LATP ceramics by a simple and reliable route.